2020
DOI: 10.1002/cta.2879
|View full text |Cite
|
Sign up to set email alerts
|

New simple transistor realizations of second‐ generation voltage conveyor

Abstract: Summary In this paper, two new complementary metal oxide semiconductor (CMOS) realizations for second‐generation voltage conveyor (VCII) are presented. The first proposed VCII has a very simple structure employing only six transistors. The second proposed VCII employs 11 transistors, and none of the transistors at both proposed circuits suffer from the body effect. Small‐signal analysis, parasitic elements, and input‐referred noise of the proposed VCIIs are given. Moreover, a new active element called voltage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 25 publications
0
22
0
Order By: Relevance
“…A number of VCII structures have been reported recently in literature [11]- [18]. Unfortunately, these structures are designed by rather high supply voltage and high-power consumption such as 1.65 V/330 µW in [11], 0.9 V/120 µW in [12], 1.65 V/320 µW in [13], 0.9 V/664 µW in [16], 0.45 V/79.3 µW in [18]. Therefore, these VCIIs are not suitable for applications to ultra-low power analog signal processing.…”
Section: Introductionmentioning
confidence: 99%
“…A number of VCII structures have been reported recently in literature [11]- [18]. Unfortunately, these structures are designed by rather high supply voltage and high-power consumption such as 1.65 V/330 µW in [11], 0.9 V/120 µW in [12], 1.65 V/320 µW in [13], 0.9 V/664 µW in [16], 0.45 V/79.3 µW in [18]. Therefore, these VCIIs are not suitable for applications to ultra-low power analog signal processing.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the dual circuit of CCII, called second-generation voltage conveyor (VCII), has attracted the attention of researchers [35][36][37][38][39][40][41][42][43][44]. In particular, the recent study reported in [35,36] showed that this device helps to benefit from CM signal processing features and overcome the limitations in CCII-based circuits.…”
Section: Introductionmentioning
confidence: 99%
“…In [17], a comparison between OA-based circuits and VCII-based circuits was drawn, showing that the problem of the cross-talk effect among inputs in a conventional OA-based non-inverting summing amplifier can be cancelled out using VCII. Literature survey shows the possibility of realizing various VCIIbased analog circuits such as filters, integrators, differentiators, rectifiers, and impedance simulators [16][17][18][19][20][21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Literature survey shows that there are very few VCII circuits designed in class AB [25][26][27]30]; however, all of them suffer from poor current drive capability. In [25], a flipped voltage follower (FVF)-based VCII circuit was presented, which can provide an output current up to ±2 mA.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation